Albendazole versus combined pyrantel pamoate-mebendazole in the treatment of mixed infection of soil-transmitted helminthiasis - Tiangsa Sembiring; Evi Kamelia; T. Ernalisna; Syahril Pasaribu; Chairuddin P. Lubis (Paediatrica Indonesiana, 2002)
Background Soil transmitted helminthiasis is still highly prevalent in Indonesia, especially in rural area and among poor socio-economic population. Helminthiasis is frequently found as a single or mixed infection. It is difficult to get a medication with better efficacy, low cost, and simple administration for all types of worms.Objective The aim of this sudy was to compare the effectiveness of albendazole and pyrantel pamoate-mebendazole combination in treating soil-transmitted helminthiasis.Methods A randomized clinical trial was perionned in September until November 1995 on students of a primary school in Tanjung Anom Village whose stool examinations showed mixed infection of helminthiasis. Subjects were randomly allocated into two groups. The A group was treated with 400 mg oral albendazole as a single dose, while the B group was treated with the combination of pyrantel pamoate 10 mg/kg body weight as a single dose and mebendazole 100 mg twice a day for three consecutive days. Cure was considered if in the stool examination, no wonn eggs were found. Statistical analysis was periormed by Chi-square test with confidence interval of 95% and p value of < 0.05 was considered significant.Results Out of 541 children, mixed infection of soil-transmitted helminthiasis was found in 374 children (69%). Three hundreds sixty-six children completed the study, consisted of 182 children in group A and 184 in group B. At 3 weeks after treatment, the cure rate in the A group was significantly better compared to that in B group.Conclusions Albendazole was more effective than the combination of pyrantel pamoate - mebendazole for treating mixed infection of soil-transmitted helminthiasis. Besides the administration was simpler and caused minimal side effect.